Comorbid anxiety and depression disorders in patients with chronic pain Transtornos ansiosos e depressivos em pacientes com dor crônica - Martha Castro; Durval Kraychete; Carla Daltro; Josiane Lopes; Rafael Menezes; Irismar Oliveira (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To evaluate the frequency of anxiety and depression disorders in patients with chronic pain. METHOD: Patients receiving care at the pain clinic of the Federal University of Bahia between February 2003 and November 2006. The MINI PLUS - Mini International Neuropsychiatric Interview was used to evaluate the patients and establish psychiatric diagnoses. RESULTS: 400 patients were evaluated mean age was 45.6±11.37 years; 82.8% were female, 17.3% male; 48.5% were married; 55.1% were Catholics; and 40.5% had only high school education. Of these 29.9% reported intense pain and 70.8% reported suffering pain daily. The most frequent medical diagnosis was herniated disc (24.5%), and 48.5% of patients had been undergoing treatment at the pain clinic for less than 3 months. Comorbidities found were depressive episodes (42%), dysthymia (54%), social phobia (36.5%), agoraphobia (8.5%) and panic disorder (7.3%). CONCLUSION: Psychiatric comorbidities are prevalent in patients suffering chronic pain. OBJETIVO: Avaliar a freqüência de transtornos ansiosos e depressivos em pacientes com dor crônica. MÉTODO: Os pacientes foram avaliados na clínica da dor da Universidade Federal da Bahia entre fevereiro 2003 e novembro 2006. O Mini-plus - entrevista neuropsiquiátrica internacional foi usado para estabelecer diagnósticos psiquiátricos nos pacientes. RESULTADOS: Foram avaliados 400 pacientes com idade média de 45,6±11,37 anos; 82,8% eram mulheres, homens 17,3%; 48,5% eram casados; 55,1% católicos; e 40,5% concluíram o segundo grau, 29,9% relataram dor intensa e 70,8% relataram sentir dor diariamente. O diagnóstico médico o mais freqüente foi hérnia de disco (24,5%), e 48,5% dos pacientes submeteu-se ao tratamento na clínica da dor por menos de 3 meses. Comorbidades encontradas foram episódios depressivos (42%), distimia (54%), fobia social (36,5%), agorafobia (8,5%) e transtorno de pânico (7,3%). CONCLUSÃO: Comorbidades psiquiátricas são predominantes em pacientes que sofrem de dor crônica.